Measuring digital health literacy and its associations with determinants and health outcomes in 13 countries - Diane Levin-Zamir; Diane Levin-Zamir; Stephan Van den Broucke; Éva Bíró; Henrik Bøggild; Lucy Bruton; Saskia Maria De Gani; Saskia Maria De Gani; Hanne Søberg Finbråten; Sarah Gibney; Robert Griebler; Lennert Griese; et al. (Frontiers in Public Health)
IntroductionDigital health information sources are playing an increasingly prominent role in health promotion, public health and in healthcare systems. Consequently, digital health literacy skills are likewise becoming increasingly important.MethodsUsing a concept validation approach, the aim of the study was to validate the digital health literacy measure HLS19-DIGI, applied in the European Health Literacy Survey (2019–2021) of the WHO M-POHL network, analyzing data from 28,057 respondents from 13 countries. The instrument is a modified and extended version of the Digital Health Literacy Instrument (DHLI).ResultsThe scale displayed high internal consistency. Confirmatory factor analysis (CFA) strengthened the hypothesized one-factor structure. In most countries, the data displayed acceptable fit to the unidimensional Rasch partial credit model (PCM). Pearson correlation with a measure of general health literacy showed sufficient discriminant validity, and a social gradient was found. Testing for predictive validity showed that the scale score predicts health-related outcomes.DiscussionThe study shows that considerable proportions of the general adult populations across countries in Europe have limited DHL skills. The level of DHL has direct potential consequences for some forms of health service utilization, in some countries. Implications of the study include recommendations for improving digital health literacy, promoting organizational health literacy and quality assurance for digital health information and resources.